(untitled) (Semiárida, 2023)
The financial lending system towards the agricultural sector has undergone significant evolution in terms of its structure and characteristics over time. The source of financing plays a fundamental role in the development and growth of the activity, providing the necessary capital to finance production, acquisition of inputs and machinery, and other related financial needs. The objective of this study is to develop an analysis of the financial loans system for the national agricultural sector and specifically to La Pampa. The results obtained indicate that the agricultural sector is approximately 16 % of the total financial loans in the national economy and 29 % in La Pampa. There is a similar trend between total loans and those in the agricultural sector, with significant growth until 2013, followed by a decline until 2016 and a rebound until 2018. The concentration of loans in the sector, particularly in crops and agricultural services, is highlighted.